Communities & Crowds: a toolkit for hybrid volunteering with cultural heritage collections - Geoffrey Belknap; Samantha Blickhan; Lynn Wray; Alex Fitzpatrick; Lincoln Anderson; Lawrence Brooks; Jacob Fox; Paulien ten Hagen; Matt Hick; Adrian Hine; Maureen Rowe; Sandra Rowe; et al. (Science Museum Group Journal)
This toolkit outlines the steps taken by the Communities & Crowds project to give ownership to local volunteers to identify photographs that reflect their interests; to digitise them to museum standards; and to share these collections with a global audience via an online crowdsourcing project. Communities & Crowds is an AHRC-funded collaboration between the NSMM (Bradford, UK), the Adler Planetarium (Chicago, IL), National Museums Scotland (NMS) (Edinburgh, UK), and Oxford University (Oxford, UK). It re-examines the role of the museum volunteer by combining participatory research methods and online crowdsourcing techniques to explore how local communities can collaborate with digital volunteers around the world to increase discoverability of, and access to, the collections that matter to them. The toolkit and accompanying downloadable templates are intended to be useable and reusable for any heritage organisation that wants to work with volunteers to find stories in photographic collections that matter to those audiences.